Channel estimation and data detection algorithms for UWB multiuser communications - Barbieri, Alessandro; Pancaldi, Fabrizio; Vitetta, Giorgio M (2010 5th International Symposium on Wireless Pervasive Computing, 2010)
In this paper, a novel ultrawideband system for multiuser data communications is proposed. At the transmit side multiple users are allowed to send pulse position modulated signals in a synchronized fashion exploiting a given frequency subband in the same time intervals. Overlapped data frames sent by distinct users include low data rate training sequences with different repetition periods. This transmission strategy, known as rate division multiple access in the technical literature, allows to ease the first two fundamental tasks at the receive side, namely joint channel estimation and timing synchronization. Channel estimates are exploited by a multiuser detector based on the Viterbi algorithm and separating the contribution generated by the user of interest from those produced by all the other co-channel users. Numerical results evidence that the proposed solution can offer an efficient usage of the available spectrum at the price of a limited complexity.